Isolation and characterization of cellulose from pomegranate (punica granatum) peel - Siddiqui, Vasi Uddin; Almehjani, Tareq Mohammed; Sapuan, S.M.; Jamal, Tarique; Ilyas, R.A.; Eldin, Sayed M; Khan, Abir; Jameel, Yusuf (Taylor and Francis Group, 2024)
A commonly wasted agricultural waste, pomegranate peel has attracted attention as a useful biomaterial with a wide range of potential uses. Fruit and vegetable wastes create environmental difficulties, as well as a loss of valuable biomass and a financial cost to enterprises, due to its high biodegradability. This study focuses on the extraction and characterization of cellulose from both the outer and inner layers of pomegranate peel. The cellulose extraction process involves a multi-step approach, encompassing delignification and mercerization. Fourier transform infrared spectroscopy (FTIR) revealed characteristic peaks associated with cellulose, confirming its presence in the extracted material. Field emission scanning electron microscopy (FESEM) depicted the morphological transformation of cellulose as non-cellulosic components were removed during the extraction process. Particle size analysis demonstrated that alkaline treatment reduced the cellulose particle size. X-ray diffraction (XRD) analysis indicated a significant increase in cellulose crystallinity due to the elimination of hemicellulose and lignin following the extraction process. The chemical composition analysis revealed that treated pomegranate peels contained higher cellulose content compared to their untreated counterparts. This study offers insightful information about the possible uses of pomegranate peel cellulose and its adaptability to a different application.